METHODS OF DEVELOPING SPEECH IN OLDER PRESCHOOL CHILDREN DURING ENVIRONMENTAL INTRODUCTION - O. T. Makhmudova; R. Mirzayeva (Web of Journals Publishing, 2025)
When exploring their surroundings (guided by educators or parents), children should not merely observe, but also examine objects, their parts and elements, perceive processes and phenomena, and reflect on them. To achieve this, the educator is tasked with employing methods such as comparison, contrast, differentiation, generalization, imitation, and other similar techniques. Additionally, during the learning process, it is important to involve older preschool children in age-appropriate types of work (cleaning small ditches, loosening soil around trees, tending to flowers).
Keywords: Environment, speech development, perception, listening comprehension, monologue, dialogue, engaging in communication, older preschool age, speech impediment, imitation.